2022
DOI: 10.3390/molecules27134242
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Content of Bioactive Compounds in Infusions Prepared from Different Parts of Wild Polish Stinging Nettle (Urtica dioica L.)

Abstract: Nettle is a common plant that offers many health benefits and is grown all over the world. The content of active compounds in roots, stems, and leaves was determined based on the extraction procedure optimized using the Central Composite Design. Flavonols, phenolic acids, trigonelline, nicotinamide, nicotinic acids, and short-chain organic acids were determined with the use of LC–MS/MS and capillary isotachophoresis. Trigonelline, which was not previously reported in the roots and stems of nettle, was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…1 and 5 ( Table 2 ). The domination of rutoside in nettle leaves was observed earlier by Devkota et al [ 17 ], Pinelli et al [ 39 ] and Jeszka-Skowron et al [ 40 ]. According to Zekowić et al [ 41 ], among flavonoids, apigenin, luteolin, and naringenin and their derivatives are also present in this raw material.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…1 and 5 ( Table 2 ). The domination of rutoside in nettle leaves was observed earlier by Devkota et al [ 17 ], Pinelli et al [ 39 ] and Jeszka-Skowron et al [ 40 ]. According to Zekowić et al [ 41 ], among flavonoids, apigenin, luteolin, and naringenin and their derivatives are also present in this raw material.…”
Section: Resultssupporting
confidence: 58%
“…In turn, Pinelli et al [ 39 ] indicated lower amounts of these substances, i.e., 138.5 mg/100 g DW and 58.9 mg/100 g DW, respectively. So far, in nettle leaves, other phenolic acids have been detected, includingcaffeic, p –cumaric, cinnamic, ferulic, sinapic, syringic, quinic and protocatechuic acids [ 40 , 41 , 42 , 43 ]. It is worth noting that phenolic acids are considered to determine health-promoting values, since they reveal antioxidant, anti-inflammatory, antilipidemic, antidiabetic and antihypertensive activity [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total flavonoid content in water, 70% ethanol, and 96% methanol was not significantly different. According to Vajic et al [ 20 ], predominant phenol in nettle leaves was rutin, but Jeszka-Skowron et al [ 32 ] research results showed that the lowest content of 3-caffeoylquinic acid or rutin was determined in nettle roots comparing with aerial parts of the plant. In general, the preference of the phenols for methanol and ethanol may be caused by their non-polar part and the aliphatic fragment of alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on Analytical Methods Paper eliminating the matrix effect, we chose a convenient and quick pretreatment method to remove the matrix of herbal tea samples. 27 First, the sample of herbal tea was centrifuged at 10 000 rpm for 10 min. Then, the collected liquid was ltered through a 0.22 mm water ltration membrane.…”
Section: Matrix Effectmentioning
confidence: 99%